Differences in bone quality and condylar head shape between patients with type 2 diabetes mellitus and non-diabetic patients - Amalia, Rahmi; Harqad, Teuku; Epsilawati, Lusi; Damayanti, Merry; Nursin, Rohmat (Faculty of Dentistry, Universitas Gadjah Mada, 2025)
This study aimed to compare bone quality—assessed through mandibular bone density—and condylar head shape between patients with type 2 diabetes mellitus (DM) and non-diabetic (non-DM) individuals, using bone histogram values derived from panoramic radiographs. An observational descriptive design with a cross-sectional approach was employed. The study population comprised all panoramic radiographic records collected during the study period. The sample consisted of 25 radiographs: 11 from male patients (DM and non-DM) and 14 from female patients (DM and non-DM), aged 40–60 years. Bone density was measured using a histogram analysis within a 4 × 4 mm region of interest (ROI) in the condylar head area, and the condylar head shape was also evaluated. Statistical analysis was subsequently performed. The findings revealed no statistically significant difference in mandibular bone density in the condylar area between DM and non-DM patients (p > 0.005). Similarly, the condylar head shape was predominantly oval in both groups. While individuals with type 2 DM tended to exhibit lower bone density values than non-DM individuals, the difference was not statistically significant. No significant differences in bone density were observed between the left and right condylar heads. However, variations in condylar head morphology were noted.